OPTIMIZING THE USE OF SOLAR ENERGY IN THE OPERATION OF INTELLIGENT WATER PUMPS FOR AGRICULTURE - Mochammad Hasymi Somaida; Alwi Alhabzi; Indra Karimah (PROCEEDING AL GHAZALI International Conference, 2023)
Technological progress is very rapid in the field of new and renewable energy. One of the renewable energy sources whose implementation and diversification has been very much is the Solar Power Plant (PLTS). There are many benefits of PLTS in various sectors, one of which is in agriculture. Nabil Aziz View Farm is a farm located in Cimanggu whose plant care is still conventional. One of the problems that exist on this farm is the provision of irrigation for the purposes of watering plants that require a lot of labor or high electricity costs. In the process of designing the system using the RAD (Rapid Application Development) method. The results obtained by making a prototype of a water pump using solar panels by utilizing solar energy for the purposes of watering plants on the Nabil Aziz View Farm can already be implemented and tested by the farm manager.